2013
DOI: 10.1016/j.bjid.2012.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Association between toll-like receptor2 Arg677Trp and 597T/C gene polymorphisms and pulmonary tuberculosis in Zahedan, Southeast Iran

Abstract: Our data suggest that 597T/C polymorphism, but not Arg677Trp polymorphism, of the TLR-2 gene is a risk factor for susceptibility to PTB in a sample of Iranian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…Moreover, in a study on an Iranian population from Zahedan, a significant difference was reported in TLR2 597T/C polymorphism genotype between patients with TB and healthy controls. However, no significant difference was reported between the groups regarding Arg677Trp (C2029T) polymorphism (30).…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, in a study on an Iranian population from Zahedan, a significant difference was reported in TLR2 597T/C polymorphism genotype between patients with TB and healthy controls. However, no significant difference was reported between the groups regarding Arg677Trp (C2029T) polymorphism (30).…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, molecular epidemiological study has shown that GT repeat variation at the microsatellite region of exon 2 of the TLR2 gene is significantly associated with an increased risk of PTB . However, molecular epidemiological study did not find any significant association of R753Q (rs5743708) and R677W (no rs number) polymorphisms of TLR2 gene with the risk of PTB in Indian and Iranian populations . Molecular studies have shown that 22 bp deletion at the promoter region of TLR2 gene is capable to alter the promoter activity .…”
Section: Discussionmentioning
confidence: 96%
“…This case-control study was performed on 188 PTB patients and 169 age-and gender-matched healthy individuals. The enrollment process and study design are described elsewhere (17)(18)(19)(20)(21)(22)(23). Briefly, the cases were chosen from PTB patients admitted to a University-Affiliated Hospital (Bou-Ali Hospital, Zahedan, Iran, referral center for TB) with no clinical symptoms or family history of TB.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the cases were chosen from PTB patients admitted to a University-Affiliated Hospital (Bou-Ali Hospital, Zahedan, Iran, referral center for TB) with no clinical symptoms or family history of TB. TB was diagnosed by clinical symptoms, posterior-anterior chest radiography, presence of acid-fast-bacilli on a sputum smear, and culturing MTB organisms from a specimen taken from the patient and response to therapy, as described previously (20)(21)(22)(23). The project was approved by the local Ethics Committee of the Zahedan University of Medical Sciences and informed consent was obtained from all subjects.…”
Section: Methodsmentioning
confidence: 99%